2023
DOI: 10.1111/bjh.18831
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for CAR‐T cell manufacturing failure among DLBCL patients: A nationwide survey in Japan

Abstract: Summary For successful chimeric antigen receptor T (CAR‐T) cell therapy, CAR‐T cells must be manufactured without failure caused by suboptimal expansion. In order to determine risk factors for CAR‐T cell manufacturing failure, we performed a nationwide cohort study in Japan and analysed patients with diffuse large B‐cell lymphoma (DLBCL) who underwent tisagenlecleucel production. We compared clinical factors between 30 cases that failed (7.4%) with those that succeeded (n = 378). Among the failures, the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The approval process for new drugs often entails rigorous and prolonged evaluation to ensure compliance with regulatory requirements. Moreover, the marketing of novel drugs necessitates a period of usage and surveillance to ascertain their effectiveness and safety [ 46 ]. It is noteworthy that the utilization of novel drugs may incur exorbitant costs that exceed the financial capabilities of ordinary households [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The approval process for new drugs often entails rigorous and prolonged evaluation to ensure compliance with regulatory requirements. Moreover, the marketing of novel drugs necessitates a period of usage and surveillance to ascertain their effectiveness and safety [ 46 ]. It is noteworthy that the utilization of novel drugs may incur exorbitant costs that exceed the financial capabilities of ordinary households [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Jo et al identified the use of bendamustine with ≥3 cycles and washout period <3 months as a high-risk factor of tisa-cel production failure. 19 …”
Section: Previous Treatmentmentioning
confidence: 99%
“… 38 It is worth noting that CD4:CD8 ratio <1:3 was identified as a risk factor of tisa-cel production failure. 19 This ratio may be affected by high quantities of monocytes, erythrocytes, or neutrophils in the apheresis product. Elavia et al showed that the contamination of cellular starting material by myeloid or erythroid cells were associated with higher quantities of CD4 + T cells, whereas CD8 + T cells were increased with neutrophils.…”
Section: Cellular Starting Materials and T-cell Fitnessmentioning
confidence: 99%
“…Even in the absence of medical complications during the vein-to-vein time, 4–7% of patients are unable to receive their CAR-T cell products as a result of manufacturing failures ( Bhaskar et al, 2021 ; St Martin et al, 2023 ), with risk factors including reduced fitness of patient T cells following multiple lines of treatment and the lengthy manufacturing process itself ( Jo et al, 2023 ). Therapeutic options following unsuccessful product manufacturing include repeating apheresis or transitioning to alternative therapies, though survival outcomes are poor in both cases ( Jagannath et al, 2021 ; Jo et al, 2023 ; Mateos et al, 2023 ). Altogether, the multiple sources of delays leading to loss of life underscore the criticality of timely access to CAR-T cell products ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%